Ending the food box program was the right move - Glauber, Joseph W. (Capitol Hill Publishing Corp., 2021)
At a recent House hearing, U.S. Department of Agriculture Secretary Tom Vilsack said that USDA would terminate the Farmers to Family Food Box program. The announcement provoked an outcry from proponents such as the Farm Bureau who had supported the popular program. But despite the program's popularity among some, USDA made the right decision. The food box program was created during the early phase of the pandemic when processing bottlenecks caused by lockdowns and COVID-19 outbreaks had upended the food distribution program in the U.S. and put millions out of work. The idea of the Food Box program was to purchase food from farmers who were having trouble marketing their produce, dairy products and other perishable items to needy families affected by the pandemic. As of March 2021, the food box program has delivered almost 150 million boxes of food to approximately 11,000 nonprofit organizations. Between $4.5 and $6 billion has been spent on the program since it went into effect last May.